Performance Analysis in WDM/TDM Passive Optical Networks - Kopuz, Birnur; Unverdi, N. Ozlem (IEEE, 2024)
In this study, a Hybrid Wavelength Division Multiplexing and Time Division Multiplexing Passive Optical Network structure with two input channels operating at frequencies of 193.1 and 193.2 THz was designed using the OptiSystem 7.0 simulation software. The effects of fiber length, input power, bit rate, number of users, and filter type on the system performance were analyzed, and the results were compared.
Keywords: Communication technologies; optical communications; passive optical network; hybrid systems; multiplexing; Computer Science; Engineering; Telecommunications